Teaching Research Methodology: Student-centered Approach Computing Education Undergraduate Course - Motjolopane, Ignitia (Ital Publication, 2021)
Teaching research methodology is one of the core components of various degree programs. Scholarship around teaching research methodology is beginning to grow with most work concentrated in Social Work, Health, Social Science, and limited work in the area computing education. This paper presents a reflection on adopting a student centred approach towards teaching research methodology course to three different groups of fourth level university students. In this paper the strategies for facilitating deep learning in teaching research methods and research methods in the Information Systems domain will be discussed. In addition, reflections on the use of a student centred approach, student experiences and strategies used. The experiences and strategies relate to facilitating deep learning. The experiences are focused on topic identification, conducting, and writing up the literature reviews, developing an understanding of the research methodology inclusive of data analysis and presenting the research report.Â Doi: 10.28991/esj-2021-01255 Full Text: PDF